The The Influence of Semendenese South Sumatra Dialect (SSSD) Towards Students’ English Pronunciation - SAS, Niro Arif; Faridi, Abdurrachman; Saleh, Mursid (English Education Journal, 2020)
In the process of acquiring L2, most of the students usually face many difficulties in pronunciation. One of the problems is L1 transfer. Therefore, the objectives of this study is to explain the influence of Semendenese South Sumatra dialect (SSSD) towards studentsÃ¢â‚¬â„¢ English pronunciation of English vowels, consonants, diphthongs, consonant clusters, to explain the effort of the teacher in developing of the studentÃ¢â‚¬â„¢s pronunciation. This study used descriptive qualitative research. The results of this study can be concluded that SSSD gives positive transfer on the final vowel sound [Ã‡Â]. Since this vowel sound existed in SSSD in words were frequently produced on final position. Moreover, SSSD did not strongly give positive transfer on studentsÃ¢â‚¬â„¢ pronunciation of English vowels [Ã‰Âª], [ÃŠÅ’], [ÃŠÅ ], [e], [Ã‰â€™], consonants [p], [b], [t], [d], [z], [k], [g], [f], [h], [s], [m], [n], [Ã…â€¹], [l], [r], [w], [j], final diphthong sounds [Ã‰â€Ã‰Âª] and [aÃŠÅ ], and consonant clusters [st], [pr], [str], and [spr]. Moreover, SSSD did not strongly give negative transfer on the substitutions of long vowel sounds [i:], [Ã‰Å“:], [Ã‰â€˜:], [u:], [Ã‰â€:], and [ÃƒÂ¦] into short vowel sounds [Ã‰Âª], [Ã‡Â], [ÃŠÅ’], [ÃŠÅ ], [Ã‰â€™], [e], consonant sounds [tÃŠÆ’], [dÃ“Â¡], [v], [Ã‰Âµ], [ÃƒÂ°], [ÃŠÆ’], [Ã“Â¡] into sounds [t], [j], [p], [f], [d], [z], and diphthong sounds [iÃ‡Â], [eÃ‡Â], [ÃŠÅ Ã‡Â], [eÃ‰Âª], [Ã‡ÂÃŠÅ ]. It occurred not only because of these sounds did not exist in SSSD sound system, but it was also influenced by spelling interference from L1 and lack of pronunciation training. Last, the effort of teacher in developing studentsÃ¢â‚¬â„¢ pronunciation was still lack and had to be improved.